(untitled) (Archives of Mechanics - Test, 2002)
Transient response of a clamped rigid-perfectly plastic circular membrane subjected to central impulse loading is formulated as a wave propagation problem. A closed-form solution for transverse deflections is derived by neglecting the radial motion as well as the circumferential stress in the constitutive law but retaining finite deflections and slopes. The final shape of the membrane is obtained in terms of the magnitude of the applied impulse and the radius of the centrally loaded area.